2002
DOI: 10.1086/343743
|View full text |Cite
|
Sign up to set email alerts
|

An Unusual Case of Pulmonary Invasive Aspergillosis and Aspergilloma Cured with Voriconazole in a Patient with Cystic Fibrosis

Abstract: The development of pulmonary aspergilloma and invasive aspergillosis is a rare complication of cystic fibrosis. We describe a 29-year-old patient with cystic fibrosis who had invasive pulmonary aspergillosis that was not cured by amphotericin B, liposomal amphotericin B, or itraconazole. This patient was subsequently successfully treated and cured with the novel antifungal agent voriconazole.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
22
1

Year Published

2005
2005
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(23 citation statements)
references
References 18 publications
0
22
1
Order By: Relevance
“…In contrast to the patient described by Chow et al [6], neither of our patients cleared the pulmonary fungus ball after several months of therapy with voriconazole, despite the in vitro susceptibility of the fungal isolates. We administered voriconazole at the standard dosage of 200 mg po b.i.d.…”
contrasting
confidence: 99%
See 2 more Smart Citations
“…In contrast to the patient described by Chow et al [6], neither of our patients cleared the pulmonary fungus ball after several months of therapy with voriconazole, despite the in vitro susceptibility of the fungal isolates. We administered voriconazole at the standard dosage of 200 mg po b.i.d.…”
contrasting
confidence: 99%
“…Voriconazole showed a remarkable efficacy in persons with invasive aspergillosis in a clinical trial [5], but there are no data yet on its efficacy in patients with aspergilloma. In a recent report, Chow et al [6] described a patient with pulmonary aspergilloma that was cured with voriconazole. The favorable outcome in this case report led us to use the drug in 2 patients with pulmonary fungus balls.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Voriconazole Efficacy of voriconazole (VRC) against IA was first demonstrated in some reports, including after the use of AmB-d, lipid formulation of amphotericin B deoxycholate, or itraconazole [32,[147][148][149]. These results were confirmed in a recent study that reported the superiority of VRC (two i.v.…”
Section: New Drugsmentioning
confidence: 74%
“…Recently, some reports have suggested that high doses of inhaled corticosteroids may also be a risk factor for IPA [31][32][33]. Explanations as to how steroids may promote IPA are discussed later (see Pathophysiology section).…”
Section: Epidemiologymentioning
confidence: 99%